ТЕХНОЛОГИИ И ТЕХНИЧЕСКИЕ СРЕДСТВА ПРИГОТОВЛЕНИЯ КОНЦЕНТРИРОВАННЫХ КОРМОВ С ИСПОЛЬЗОВАНИЕМ СОЕВОГО БЕЛКА (World Science, 2016)
The article presents the modern technology of extruded feed. Given the main indicators of quality of the extrudate. Based on the above analysis, it developed a classification that allows to identify the most promising direction in the development and creation of the press - extruder for the preparation of animal feed with soy protein. Thus, the analysis showed that the most efficient implementation of the process of preparation of mixed fodders by extruding a mixture of cereal and soy components with an insoluble residue, as a result of the extrusion is a qualitative mixing of feed and barothermal processing.